2019
DOI: 10.1111/exd.13835
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for neurogenic inflammation in lichen planopilaris and frontal fibrosing alopecia pathogenic mechanism

Abstract: Lichen planopilaris (LPP) and frontal fibrosing alopecia (FFA) are lymphocytic scarring alopecias affecting primarily the scalp. Although both diseases may share some clinical and histopathological features, in the last decade, FFA has become an “epidemic” particularly in Europe, North and South America with unique clinical manifestations compared to LPP, thus, raising the idea that this disease may have a different pathogenesis. Symptoms such as scalp burning, pruritus or pain are usually present in both dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 11 publications
1
22
0
2
Order By: Relevance
“…It is important to note that Substance P receptor neurokinin (NK1) localizes to caveolae and that caveolae disruption in either cells (by cyclodextrins) or in Cav1 knockout mice significantly reduces Substance P immunoreactivity and activation of NK1 receptor [ 84 ]. Since perifollicular neurogenic inflammation, in which substance P plays a key role [ 85 ], has recently been recognized as an additional feature of FFA pathobiology [ 2 ], the possibility that Cav1 may facilitate substance P-induced bulge IP collapse deserves careful exploration ( Figure 1 b). Considering that Substance P and IFN-γ have been previously demonstrated to be upregulators of MHC-I and to rapidly induce HF-IP collapse [ 73 , 74 ], this further substantiates our hypothesis that downregulation of Cav1 may be an alternative approach to inhibit collapse HF immune privilege and thus be a potential avenue for treatment of FFA.…”
Section: Premisesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that Substance P receptor neurokinin (NK1) localizes to caveolae and that caveolae disruption in either cells (by cyclodextrins) or in Cav1 knockout mice significantly reduces Substance P immunoreactivity and activation of NK1 receptor [ 84 ]. Since perifollicular neurogenic inflammation, in which substance P plays a key role [ 85 ], has recently been recognized as an additional feature of FFA pathobiology [ 2 ], the possibility that Cav1 may facilitate substance P-induced bulge IP collapse deserves careful exploration ( Figure 1 b). Considering that Substance P and IFN-γ have been previously demonstrated to be upregulators of MHC-I and to rapidly induce HF-IP collapse [ 73 , 74 ], this further substantiates our hypothesis that downregulation of Cav1 may be an alternative approach to inhibit collapse HF immune privilege and thus be a potential avenue for treatment of FFA.…”
Section: Premisesmentioning
confidence: 99%
“…Primary lymphocytic cicatricial alopecias (PLCA) are characterized by progressive, permanent hair loss for which there is currently no cure [ 1 , 2 , 3 , 4 ]. PLCA result from irreversible damage to the epithelial stem cells (eSCs) of the hair follicle (HF) due to (1) eHFSC apoptosis, (2) pathological epithelial-mesenchymal transition (EMT), (3) collapse of bulge immune privilege (IP) and (4) interferon-gamma-dominated Th1-type chronic inflammatory response [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the presence of more pronounced follicular inflammation and perifollicular fibrosis in the clinically unaffected area is not surprising, given the fact that the AB is an evolved presentation of the disease and studies have shown that the clinically unaffected skin in lichen planopilaris is histologically affected. 8 The main limitation of this study is the lack of control group. However, as both biopsies were taken from the same scalp, we were able to study also the differences between clinically affected and unaffected areas.…”
mentioning
confidence: 95%
“…Doche and colleagues demonstrate that perifollicular lymphocytic inflammation can be observed in overtly unaffected scalp skin of LPP and frontal fibrosing alopecia (FFA) patients . The data suggest a much more generalized inflammation is present, extending well beyond the lesion limit.…”
Section: Scarring Alopeciamentioning
confidence: 99%
“…And/or something else in the local environ that decides where lesions will develop? In fact, Doche et al also characterize the presence of neurogenic inflammation in LPP and FFA both within and beyond the alopecic lesions . They observed differences in neuropeptide distribution, in LPP versus FFA.…”
Section: Scarring Alopeciamentioning
confidence: 99%